The Effects of Movie-Enriched Extensive Reading on TOEFL IBT Vocabulary Expansion and TOEFL IBT Speaking Section Score - Soran Abubakr Abdulrahman; Saban Kara (Anı Publishing, 2023)
A wealth of research has been conducted to compare extensive and intensive reading thanks to their increasing popularity in educational settings globally. However, only a limited number of studies have been conducted to measure the effects of movie-enriched extensive reading activities. To this aim, the present study was undertaken to investigate the effects of movie enriched extensive reading on freshman students` TOEFL IBT vocabulary expansion and TOEFL IBT speaking section scores. In this regard, 40 students studying at an international private university in Erbil, Iraq was divided into two groups using a stratified random sampling method. Control group students (N=20) read and analyzed six graded readers by employing intensive reading, whereas experimental group students (N=20) actively participated in reading prominent novels and watching movie versions of them. A mixed methods design was employed to gather qualitative and quantitative data, respectively, so they were utilized to make better interpretations. Quantitative data were collected through 2 vocabulary and speaking exams related to TOEFL IBT as pre-test and post-test. Additionally, qualitative data were collected through interviews. Results of the independent samples t-test revealed that experimental group students` speaking and vocabulary scores increased significantly, whereas they were not significant enough in the control group. Moreover, students` attitudes towards reading novels and watching movies changed positively based on the interview transcripts. In light of the findings, this study may have some implications for researchers, educators, and authorities seeking opportunities to integrate extensive reading into the curriculum.